2008
DOI: 10.1177/1352458508090221
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer atrophy is associated with physical and cognitive disability in multiple sclerosis

Abstract: Background Studying axonal loss in the retina is a promising biomarker for multiple sclerosis (MS). Our aim was to compare optical coherence tomography (OCT) and Heidelberg retinal tomography (HRT) techniques to measure the thickness of the retinal nerve fiber layer (RNFL) in patients with MS, and to explore the relationship between changes in the RNFL thickness with physical and cognitive disability. We studied 52 patients with MS and 18 proportionally matched controls by performing neurological examination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
96
2
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(118 citation statements)
references
References 40 publications
11
96
2
8
Order By: Relevance
“…Although the patterns of RNFL loss are different in ON compared with other diseases such as glaucoma, with the highest degree of RNFL loss in the temporal quadrant, 10,23 our findings are similar to that previously observed in glaucoma patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although the patterns of RNFL loss are different in ON compared with other diseases such as glaucoma, with the highest degree of RNFL loss in the temporal quadrant, 10,23 our findings are similar to that previously observed in glaucoma patients.…”
Section: Discussionsupporting
confidence: 89%
“…From a clinical point of view, patients who are part of clinical trials that require a high degree of consistency with RNFL thickness measurements may not be able to interchange between Stratus-and Cirrus-OCT. Perhaps, in the case of switching from Stratus-to Cirrus-OCT technology, the best strategy for switching from one to the other during the follow-up of a patient may be to perform a follow-up Stratus scan to determine whether there has been a change from prior Stratus scans and then perform a new baseline scan with Cirrus for future comparison. 10 In conclusion, our findings show that RNFL thickness measurements by Cirrus HD-OCT and Stratus-OCT were different in patients having ON, although the two measurements were well correlated. Stratus measurements are generally higher than Cirrus, except at thinner RNFL values.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Investigating focal cortical volume patterns might help to identify regions that are important hubs in functional or structural networks and might contribute to the disability of MS patients. Previous studies indicated, that impairment of visual function might be as well associated with cognitive function in MS (Toledo et al., 2008; Wieder et al., 2013). The purpose of this study was to investigate to what extent OCT measures correlate with cortical areas that are not part of the primary visual system, and to explore if there is a distinctive pattern of association with cortical regions and if these associations might be linked to neuropsychological performance.…”
Section: Introductionmentioning
confidence: 99%
“…119 Studies have shown significant correlations between RNFL atrophy and cognitive disability, in particular attention and executive deficits, assessed using the symbol digit modality test in patients with MS when compared with healthy controls. 121 These findings may be explained by the reported correlations between RNFL thickness and brain atrophy. 122,123 Not all studies have found the same, however, others have reported an association between cognitive impairment in MS patients and performance in visual function tests such as low contrast sensitivity testing.…”
mentioning
confidence: 98%